Teachers' questioning strategies and its effects on the students' classroom participation. - Militar, Jennifer Jeanne D (2000.)
This study was undertaken to determine the effects of a teacher's questioning strategy on the students' classroom participation. It investigated whether there was a difference in the responses of students when asked affective and cognitive questions. It also intended to find out whether there was a signifiant interaction between types of question asked and questioning strategies used during classroom discussions. A pre-test was conducted to identify the three most common questioning strategies that were used in the experiment. Sixty (60) students, enrolled in Psychology courses for the second semester, were randomly selected and randomly assigned to three groups with a corresponding questioning strategy used in the discussion. A film episode from the Discovery Channel's Medical Detectives was shown and the discussion, during which questioning strategies were used in asking affective and cognitive questions about the film and the participants' response to them. From it the responses were evaluated. This was analyzed using the Repeated Measures Analysis Variance (ANOVA). The results showed that for both the frequency and quality of classroom participation, only the types of question, (affective vs. cognitive) were found to be significantly different. The total mean score of the frequency of responses (X1=6.44) to cognitive questions were greater than that of affective (X2=2.90) quations. For the quality of responses, the totalmean score (X1=6.53) of the responses to cognitive questions were also greater than that of affective (X2=4.31) questions.
Research Paper (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Students -- Classroom Participation